DETAILED ANALYSIS OF 30 FERTELIZER DEMONSTRATIONS IN SOUTHERN THAILAND - J. Dootson; J.R.J. Moss; Sura Rungreung; Saowannee Meemuth; K. Ryder; Maliwan Rattanapruk (International Coconut Community, 1990)
Twice‑yearly coconut counts taken from 30 different demonstrations on Thai Tall palms showed that applying fertilizer increased the number of nuts produced over the 3 years studied. Application of 2kg of a 13:13:21 NPK compound was ‑shown to be more cost effective than applying 4kg of the same compound, but was rarely profitable, as the largest responses occurred in years when yields were high and the farmgate prices were at their lowest. Sites where nut counts from unfertilized plots were high showed much smaller responses to applied fertilizer than those having lower counts, suggesting that inherently low yielding plots are more likely to respond to applied fertilizer. Nut counts can be considered a simple, cheap and reliable method of anticipating the probability of a fertilizer response.